Analisis Resepsi Remaja Perempuan Mengenai Peran Ayah dalam Video Klip “Saat Kau Telah Mengerti” - Wibowo, Fauzan Afif; Dyah Kusumawati (Research and Community Service UNIVERSITAS KALBIS, 2024)
Fathers have a role as head of the household and are involved un childcare. The presence of fathers for their children has closeness that is not only physical but emotional. Especially for girls. This study aims to determine the reception of adolsecent girls in Jakarta regarding the role of fathers in the video clip entitled “Saat Kau Telah Mengerti”. This research uses the contrutivism paradigm with qualitative approach. The research method used reception analysis, and Stuart Hall’s encoding decoding theory to see three audience positions of dominat hegemony, negotiation and oppotition. The result showed that three informants were in the dominant hegemony position regarding the role of the father because they had an attachment to the informant’s experience, while two informants were in the negotiation position because of the informant's experience of being abandoned by his father.